Adultery Crimes From The Perspective Of Islamic Law And Customary Law In Dolok District, North Padang Lawas Regency - Perantoan Rambe; Sahmiar Pulungan (CERED Indonesia Institute, 2023)
Violation of Islamic law and customary criminal law is still viewed as something that can cause disruption and disturb the consciousness of the community. The purpose of this research is to examine and analyze legally how the regulation of adultery is based on Islamic law and customary law in Dolok District, Padang Lawas Utara Regency, to understand and analyze legally the application of customary criminal sanctions against perpetrators of adultery in Dolok District, Padang Lawas Utara Regency, and to examine the authority of customary leaders in resolving cases of adultery in Dolok District, Padang Lawas Utara Regency. The type of research used is qualitative research with data collection techniques, including interviews with customary leaders in Dolok District, Padang Lawas Utara Regency. The results of this study indicate that the regulation of customary sanctions for adultery in customary law is called